Optimizing the Performance of the Samapta Unit to Prevent the Criminal Act of Theft with Agraming in the Jurisdiction of Polresta Pati - Asyrof, Muhammad Naufal (Advances in Police Science Research Journal, 2024)
The number of cases of theft by weighting in the jurisdiction of Polresta Pati was ranked first with the highest number among other cases of theft, curas, and theft by weighting (3C). This indicates that it is known that the Samapta Polresta Pati Unit has not been able to achieve its objective optimally, namely to maintain public security and order. This research focuses on the implementation of patrols and efforts to increase patrols by the Pati Police Samapta Unit in preventing criminal acts of theft by weighting. The method used in this study uses a qualitative approach, with the aim of obtaining complete and actual facts, which are reviewed by the optimization concept, the patrol concept, the theft concept by weighting. The theory used in this study is Management Theory using POAC (Planning, Organizing, Actuating, Controlling and SWOT analysis theory (Strength, Weakness, Opportunities, Threat). The research results obtained indicate that there are still a number of obstacles experienced by the Samapta Polresta Pati Unit in patrol activities ranging from limited human resources, ineffective patrol time, minimal allocation of patrol funds, and less than optimal use of police technology. It can be concluded that the implementation of patrols by the Pati Police Samapta Unit cannot be said to be optimal. This is because some of the patrol implementation processes cannot be fully implemented. The organizational resources of the Pati Police Samapta Unit in preventing criminal acts of theft by weighting can also be said to be not ideal. It is recommended for the Samasta Polresta Pati Unit to optimize and improve the implementation of patrols by conducting special guidance, utilizing organizational resources at the Samasta Polresta Unit such as creating special modules, conducting outreach to the community, making patrol programs more efficient.